The Angiotensin converting enzyme gene I/D polymorphism in Polish rowers - Cieszczyk, P.; Krupecki, K.; Maciejewska, A.; Sawczuk, M. (International Journal of Sports Medicine, 2009)
Angiotensin converting enzyme gene (ACE) is the most frequent investigated gene in the context of genetic conditioning of sports-predispositions. Product of this gene is a key-element in the renin-angiotensin system responsible for the regulation of blood pressure. In this study DNA polymorphism in the ACE gene was studied in Polish rowers in order to examine the hypothesis that ACE genotype is associated with athletes performance. Fifty-five male Polish rowers including Olympic and World champions were recruited for this study. Control samples were prepared from 115 unrelated volunteers. PCR amplification of the insertion (I) or deletion (D) fragment of ACE gene was performed. Genotype distribution and allele frequencies were determined by genotype and gene counting. Significance was assessed by ?2 analysis. ACE genotype distributions amongst subjects and controls were in Hardy-Weinberg equilibrium. Compared with controls, the frequency of I allele differ significantly from that found in rower's group: 56.3% vs. 44.3%, (P=0.038) and ACE genotype frequency amongst the whole athletes group (30.9% II, 50.9% ID, 18.2% DD) was also different from expected values (control group 19.1% II, 50.4% ID, 30.4% DD; P=0.039). This data confirm a positive association of the I allele of ACE gene with endurance.